Conceptualization of Psychocide and Psychoethnicide: Power Struggle, Socioeconomic Conditions Deterioration and Mental Health Degradation in Post-Genocide Rwanda - Evariste Erwin Sebahutu (International Journal of Child Development and Mental Health)
The dynamic evolution of military strategy has highlighted the role of psychological manipulation, leading to the emergence of psychological warfare. This strategy utilizes propaganda and psychological operations (PSYOPs) to influence human cognition and decision-making, particularly through mass media. In military conflicts, these techniques are employed to demoralize enemies with false information. Notably, psychological torture or non-touch torture methods have been effective in extracting information from prisoners but come with severe health consequences such as Post Traumatic Stress Disorder (PTSD). The rise of military regimes and oligarchies, particularly in economically disadvantaged nations, has seen these psychological tactics employed domestically, leading to extreme poverty, human rights abuses, and concealed oppression techniques like gender washing and sports washing. This results in severe social distress hence deteriorating mental health. This deliberate infliction of mass mental harm by a small elite group pursuing absolute power was termed “Psychocide.” In ethnocratic regimes, these tactics target specific ethnic groups, leading to trans-generational mental health deterioration and related consequences, a phenomenon termed “psychoethnicide.” This paper aims to provide a conceptual framework to understand “psychocide” and “psychoethnicide” concepts which are forms of social groups and ethnicity -based psychological warfare and propaganda and show how these practices contribute to the increasing burden of mental disorders in targeted populations. A scoping review of the literature was complemented with the analysis of social media artifacts to examine the patterns of psychological warfare and its mental health implications in Rwanda. The findings highlight the pervasive nature of group and ethnic-based psychological manipulation, revealing its significant role in exacerbating mental health issues.